Knowledge asset taxonomy for public institutions of higher learning corporate memory (case study of UiTM curriculum review) / Suzana Basaruddin - Basaruddin, Suzana (2019)
Tertiary education system in Malaysia has undergone a series of changes in the early 21st century to place the Malaysian education on the global map. While trying to achieve high expectations from their stakeholders, the Public Institutions of Higher learning (PIHL) are facing difficulties in managing its own Knowledge Assets (KA) due to the complexity of the knowledge. One of the pertinent knowledge that is critical to manage in PIHL, is the curriculum review (CR) knowledge. Managing CR knowledge is necessary in ensuring PIHL members able to understand and apply the knowledge to fulfil their tasks and responsibilities related to curriculum management. Corporate Memory (CM) was identified as one of appropriate tools in managing PIHL KA. The KA in PIHL CM should be reflected by its KA structure in order to facilitate understanding and navigation. However, the KA structure that are the contents of CM was given less attention in previous CM framework. Appropriate structure of KA in CM shall optimize the function of CM in providing centralize repository for PIHL. In order to structure the KA, the available KA structuring process has been explored. The knowledge structuring processes was found in three main domains that are Information System, Information Management and Organizational Management.